Valuing Black Lives: A Case for Ending the Death Penalty - Hoag, Alexis (2020)
Since Furman v. Georgia, capital punishment jurisprudence has equipped decisionmakers with increased structure, guidance, and narrowing in death sentencing in an effort to eliminate the arbitrary imposition of death. Yet, these efforts have been largely unsuccessful given the wide discretion built into capital sentencing which allows for prejudice, bias, and racism to persist. Juries continue to sentence a disproportionately high number of defendants who have been convicted of murdering white victims to death. As a result, death sentencing schemes tend to undervalue Black murder victims’ lives. Any effort to eliminate the disparity must center on the undervaluation of Black lives. This Article suggests that the next challenge to the death penalty should be on equal protection grounds based on the undervaluation of Black lives. It highlights that the Fourteenth Amendment was originally intended, in part, to extend the equal protection of the laws to Black victims of crime. The Article then explores the pitfalls of other race-based challenges to the death penalty. And demonstrates that a challenge based on disparities in capitally prosecuting white and Black victim cases could end capital punishment. The Article concludes with a road map for what a challenge based on the undervaluation of Black lives would look like